Oxford Reading Tree TreeTops Chucklers: Level 8: Don't Eat Soup with your Fingers level 8 : don't eat soup with your fingers - Foster, John. ([S.l.] : Oxford University Press, 2014)
Don't Eat Soup with your Fingers is filled with poems and jokes. Find out what's worse than being eaten alive by spiders and why a cat makes a better hat than a cow. Chucklers is a series of funny novels, short stories, anthologies and comics that make reading a pleasure for 7-11 year olds. There is something for everyone in this varied collection which is packed with fantastic illustrations. Books contain inside cover notes to support children in their reading. Help with children's reading development also available at www.oxfordowl.co.uk. The series is written by top children's authors and edited by award-winning author Jeremy Strong. The books are finely levelled, making it easy to match every child to the right book.